A marine thruster’s model identification based on experimental-simulation approach - Abdelmalek Laidani; Mohamed Bouhamida; Zakaria Bellahcene (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
In recent years, underwater vehicles play a very important role in the marine field, and tasks cannot be accomplished quickly and accurately without the use of such devices. Despite the progress achieved, these vehicles still have prob- lems with their controls in order to have a very good dynamic positioning or a path tracking accurately, and these problems have a direct link to their thrusters, either by negligence or by ignorance of its mathematical model. Several works were carried out to have an accurate model of them, but its behavior is still diffi- cult to be described and it strongly influences the behavior of a vehicle in which it is integrated. In this work we try to deal this problem in the aim to iden- tify a marine thruster designed by us using a low-cost test bench and a hybrid identification approach, which combines the both experimental and simulation parts. The thruster will be integrated on a remotely operated vehicle under devel- opment by AVCIS-Lab to make simulation using UUV (unmanned underwater vehicle) Simulator and ROS (Robot Operating System) toolbox under Matlab. The outcomes will be presented at the end of this paper.